SHINIGAMI DALAM KOMIK BLEACH - Yunix Citra Widara, Ni Putu (Humanis, 2016)
This research entitles “ The Shinigami in Comic Bleach ”. The reason for this title was choosen because in comic Bleach consist of many aspect that related with shinigami or  the grim reaper in Japanese myth. The purpose of this research are to know the depiction and task of shinigami in comic Bleach . This research are using Descriptive Analysis and Informal Method. The theories used are Structuralism Theory and Semiotics Theory by Marcel Danesi There are various kind of shinigami that can be found as the result of this research, each with different depiction. First, the shinigami who has a military power. Second, the shinigami who use a gigai (an artificial body), Third, the shinigami who able to transform into an animal, and the shinigami who has a hollow (bad spirits) power in their own body. Based on their depictions, their tasks also different. There are five kinds of task that shinigami do in the comic. First, the shinigami who has a task as a fighter and pure the spirits before that spirits make a mischief. Second, the shinigami who has a task as a planner and giving command to other shinigami. Third, the shinigami who has a task as a punisher troops and the execution giver. Forth, the paramedic shinigami, and fifth the shinigami who has a task as a technology developers.
Keywords: semiotics, myth, shinigami.